HUBUNGAN DUKUNGAN KELUARGA DENGAN KECEMASAN PADA IBU HAMIL TRIMESTER III DI PUSKESMAS KALIJAGA KOTA CIREBON - Taniya; Jaelani; Citra Setyo Dwi Andhini; Yanti Susan (LPPM ITEKES Mahardika, 2021)
Family support is a process of relationship between the family and its social environment that is accessible to families that can be supportive and provide help to family members Anxiety (Ansiety) is a feeling of fear that is not clear and is not supported by the situation. Pregnancy is an event that occurs in a woman from the process of fertilization (conception) to the birth of a baby. The purpose of this study was to determine the relationship of family support with anxiety in third trimester pregnant women in the Kalijaga Health Center, Cirebon City. This research method uses quantitative descriptive correlational research, with cross sectional method carried out on 30 respondents at Kalijaga Health Center in Cirebon City with independent variables of family support and anxiety dependent variables in trimester III pregnant women by using questionnaire sheet measurement tools. Data analysis used the Spearman rank test. The research place was at the Kalijaga Public Health Center, Cirebon City. The results showed that the P value is smaller than alpha, which means that Ho is rejected and Ha is accepted, so it can be concluded that there is a significant relationship between family support and anxiety in third trimester pregnant women at the Kalijaga Health Center in Cirebon City, P value 0.017 is smaller than alpha 0, 05. Nurses are expected to be able to perform their roles optimally as providers of nursing care, advocates, educators, coordinators, and collaborators in providing family support to pregnant women who experience anxiety.